Device for Sorting Silk Cocoons on Qualitative Signs (Eurasian Scientific Herald, 2023)
A device has been developed that allows simultaneously determining seven qualitative characteristics of cocoons: silkiness, shell stiffness, degree of maturity, shell thickness, shell density, cocoon volume and specific volume. In addition, cocoons can be sorted into the following three types: normal, capercaillie (having a large specific volume) and immature (according to the degree of maturity).